Prevalence of Gender Based Violence among Pregnant Women: A Hospital Based Study - Chaudhary, Pushpa; Chaudhary, Shrawan Kumar; Shrestha, Madhu (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5072 NJOG 2010 Nov-Dec; 5(2): 17-22